YODA-HSP90 Module Regulates Phosphorylation-Dependent Inactivation of SPEECHLESS to Control Stomatal Development under Acute Heat Stress in Arabidopsis - Samakovli, Despina; Tichá, Tereza; Vavrdová, Tereza; Ovečka, Miroslav; Luptovčiak, Ivan; Zapletalová, Veronika; Kuchařová, Anna; Křenek, Pavel; Krasylenko, Yuliya; Margaritopoulou, Theoni; Roka, Loukia; Milioni, Dimitra; et al. (Molecular plant, 2020)
Stomatal ontogenesis, patterning, and function are hallmarks of environmental plant adaptation, especially to conditions limiting plant growth, such as elevated temperatures and reduced water availability. The specification and distribution of a stomatal cell lineage and its terminal differentiation into guard cells require a master regulatory protein phosphorylation cascade involving the YODA mitogen-activated protein kinase kinase kinase. YODA signaling results in the activation of MITOGEN-ACTIVATED PROTEIN KINASEs (MPK3 and MPK6), which regulate transcription factors, including SPEECHLESS (SPCH). Here, we report that acute heat stress affects the phosphorylation and deactivation of SPCH and modulates stomatal density. By using complementary molecular, genetic, biochemical, and cell biology approaches, we provide solid evidence that HEAT SHOCK PROTEINS 90 (HSP90s) play a crucial role in transducing heat-stress response through the YODA cascade. Genetic studies revealed that YODA and HSP90.1 are epistatic, and they likely function linearly in the same developmental pathway regulating stomata formation. HSP90s interact with YODA, affect its cellular polarization, and modulate the phosphorylation of downstream targets, such as MPK6 and SPCH, under both normal and heat-stress conditions. Thus, HSP90-mediated specification and differentiation of the stomatal cell lineage couples stomatal development to environmental cues, providing an adaptive heat stress response mechanism in plants.
Keywords: signální transdukce; Cell Differentiation; Gene Expression Regulation, Plant; epigeneze genetická; Protein Binding; MAP kinasy kinas (kinas); heat stress; Phosphorylation; Epigenesis, Genetic; buněčné dělení; Signal Transduction; mutace; mitogenem aktivované proteinkinasy kinas; Arabidopsis Proteins; Cell Division; HSP90; Cotyledon; MAPK; proteiny tepelného šoku HSP90; proteiny huseníčku; Cell Lineage; transkripční faktory bHLH; Mitogen-Activated Protein Kinases; kotyledon; MAP Kinase Kinase Kinases; buněčný rodokmen; Mutation; reakce na tepelný šok; Basic Helix-Loop-Helix Transcription Factors; regulace genové exprese u rostlin; vazba proteinů; průduchy rostlin; mitogenem aktivované proteinkinasy; Plant Stomata; Heat-Shock Response; stomata; fosforylace; buněčná diferenciace; Mitogen-Activated Protein Kinase Kinases; Arabidopsis; HSP90 Heat-Shock Proteins